UJI VALIDITAS DAN RELIABILITAS TERHADAP BUTIR ITEM KUESIONER MINDFULNESS FOKUS ASPEK EMOSI PADA REMAJA DENGAN MASALAH MENTAL EMOSIONAL DI KLINIK TALENTA CENTER BEKASI - Andi Anggraini Syarifuddin (2022)
Emotional mental problems are one of the mental health problems that need more attention, especially for adolescents because their emotional regulation is relatively immature. Prolonged mental emotional problems can cause physical illness, intellectual decline, somatic disorders, and depression. Therefore, an intervention to overcome this problem is done, one of which is mindfulness therapy. This study aims to test the validity and reliability of the emotional mindfulness questionnaire. Data were collected through the total sampling method on 30 patients at the Talenta Center Clinic Bekasi who met the inclusion criteria, namely patients with mental emotional problems (depression, anxiety, self-harm, ADHD, OCD), patients aged 10-24 years, and patients with mental problems. emotional patients who have received mindfulness therapy at least 5 times. The exclusion criteria were patients who did not agree to fill out the questionnaire and patients who did not fill out the questionnaire completely. This type of research is descriptive quantitative with a cross-sectional research design. The results of the validity test showed that 16 items of the questionnaire were valid with r count > r table (0.3610) and the other 6 were invalid with r count < r table (0.3610). The results of the reliability test on the 16 items showed reliability with Cronbach alpha coefficient > 0.7. The emotional aspect of the mindfulness questionnaire has good validity and reliability test results, so it is suitable to be used as a research instrument. The results of this study are also supported by Baer et al. (2006); Feldman et al. (2007); and Santarnecchi et al. (2014) who found that mindfulness practices were able to increase the ability to regulate emotions. However, further research is still needed to revise and retest invalid items.